Acute physiological and perceptual responses to moderate intensity cycling with different levels of blood ﬂow restriction - Wei, Jia; Nassis, George P.; Gu, Zhengqiu; Zou, Yongdi; Wang, Xiaolu; Li, Yongming (Biology of Sport, 2021)
The aim of this study was to compare: i) the physiological and perceptual responses of low-load exercise [(moderate intensity exercise (MI)] with different levels of blood flow restriction (BFR), and ii) MI with BFR on the bike with high intensity (HI) exercise without BFR. The protocol involved large muscle mass exercise at different levels of BFR, and this differentiates our study from others. Twenty-one moderately trained males (age: 24.6 ± 2.4 years; VO2peak: 47.2 ± 7.0 ml. kg-1.min-1, mean ± sd) performed one maximal graded exercise test and seven 5-min constant-load cycling bouts. Six bouts were at MI [40% peak power (Ppeak), 60%VO2peak], one without BFR and five with different levels of BFR (40%, 50%, 60%, 70%, 80% of estimated arterial occlusion pressure). The HI bout (70%Ppeak, 90%VO2peak) was without BFR. Oxygen uptake (VO2), heart rate (HR), blood lactate (BLa), rate of perceived exertion (RPE), and tissue oxygen saturation (TSI) were recorded. Regardless of pressure, HR, BLa and RPE during MI-BFR were higher compared to MI (p < 0.05, ES: moderate to very large), and TSI reduction was greater in MI-BFR than MI (p < 0.05, ES: moderate to large). The responses of VO2, HR, BLa, RPE and TSI induced by the different levels of BFR in MI-BFR were similar. Regardless of pressure, the responses of VO2, HR, BLa and RPE induced by MI-BFR were lower than HI (p < 0.05), except for TSI. TSI change was similar between MI-BFR and HI. It appears that BFR equal to 40% of arterial occlusion pressure is sufficient to reduce TSI when exercising with a large muscle mass.